Levels of substance use among young brazilian adults during the pandemic period by COVID-19 - Silva, Giovana Alves Martins da; Reichert, Richard Alecsander; Adrião, Silvia Maria de Freitas; Baptista, Amanda Simões; Vasconcelos, Maria Luiza de Lima; Micheli, Denise De (Seven Editora, 2023)
The pandemic caused by the novel coronavirus has brought with it several challenges not only the emergency development of pharmacological measures to cope but also a unique scenario of health, political, economic, and social crisis, not to mention possible effects that are yet to emerge. Given this scenario, the objective of this study was to evaluate the impacts of Covid-19 on the behavior of alcohol and medication use of young Brazilian adults between 18 and 30 years of age in the pandemic period from March 2020 to March 2022. To this end, an online study was conducted in which a questionnaire was applied with sociodemographic questions and questions about COVID-19 as well as, to know the levels of alcohol use, the AUDIT-C was used, followed by questions about the consumption of anxiolytics, hypnotics, and analgesics. Results: The study included a sample of 247 people, mostly women from the southeast region of the country, with socioeconomic levels A / B. As for COVID-19, participants signaled difficulty in following online activities during the pandemic period as a whole (38%); in the same way that anxiety due to isolation during the entire pandemic period was observed in 41.7% of the sample; nervousness or restlessness was also observed by isolation mainly during the first pandemic year by 22.7% of the sample and stress was observed throughout the pandemic period by 43% of the sample. Regarding the use of substances during the pandemic, it was observed that most participants did not use anxiolytics (60.7%) or hypnotics (72.1%), while a significant portion used analgesics or muscle relaxants (58%) prescribed (12.2%) or not prescribed (45.8%). Regarding alcohol consumption, use was reported by 16.6% of the sample in the first pandemic period and an increase to 19.8% considering the entire pandemic period. DOI:https://doi.org/10.56238/emerrelcovid19-010